(untitled) (Research, Society and Development, 2021)
This is a systematic review of clinical trials, carried out from July to August/2020 in four databases. The selection of articles took place in two phases by two researchers independently and in pairs. The risk of bias was assessed by Cochrane guidelines in Review Manager version 5.5. Thus, the study aimed to evaluate the effectiveness of interventions in reducing screen time in adolescents. Thus, four articles that met the eligibility criteria for inclusion and analysis were included. With regard to screen types, the following were addressed in the studies: television, video game, computer and cell phone. Interventions that involved physical activity were more effective, however, meditation had more beneficial effects on secondary outcomes such as decreased smartphone addiction and stress levels, as well as improved self-control and stress coping strategies. Therefore, the interventions used in the studies were partially effective since, after the intervention period, the adolescents again showed an increase in exposure time.